Investigating tourist visit behavior in Bengkulu, Indonesia: The role of satisfaction, trust, and price - Syofian; Markoni; Fauzan; Idham Lakoni (Journal of Economics and Business Letters, 2023)
Bengkulu, a rapidly developing tourism destination in Indonesia, presents a unique context for understanding tourist behavior. This study investigates the influence of satisfaction, trust, and price on tourist visit behavior in Bengkulu. Using a sample of 340 tourists and employing Structural Equation Modeling (SEM), the study tests the relationship between these variables. Results indicate that both satisfaction and trust have a significant positive impact on visit behavior. However, the price does not significantly influence visit behavior. These findings underscore the importance of enhancing tourist satisfaction and building trust to improve visit behavior in Bengkulu. The findings also suggest that price, in this particular context, might not be a crucial determinant for tourists' decisions to visit. This study contributes to the literature on tourist behavior and provides practical implications for destination marketing in Bengkulu and similar emerging tourist destinations.